Association of overweight/obesity and digestive system cancers: A meta-analysis and trial sequential analysis of prospective cohort studies - Ji Ren; Chunyan Tang; Jinghe Wang; Yanan Wang; Dongying Yang; Jianming Sheng; Shili Zhu; Yunli Liu; Xiaoqi Li; Wei Liu (PLoS ONE, 2025)
Background Previous researches have reported correlations between overweight/obesity and common digestive system cancers (DSCs), including gastric, liver, esophageal, colorectal, and pancreatic cancers. However, the inconsistency in defining overweight/obesity and the risk of recall bias from case-control and retrospective cohort studies may influence existing results. Therefore, we aimed to validate the relationship between overweight/obesity and common DSCs by combining prospective cohort studies based on the World Health Organization (WHO) criteria for defining overweight/obesity. Methods A comprehensive literature search was conducted across PubMed, Embase, Web of Science, and Cochrane databases, covering all publications up to February 7, 2024. The inclusion criteria focused on prospective cohort studies that examined the link between overweight/obesity and risks of DSCs. R software 4.1.3 and STATA 12 were utilised to calculate the relative risk (RR), with 95% confidence interval (CI) and prediction interval (PI). TSA v0.9.5.10 Beta software was used for trial sequential analysis (TSA). Results The meta-analysis encompassed 39 articles. The overall analysis showed that compared with normal weight, overweight/obesity increased the risks of liver cancer (overweight: RR [95% CI] =  1.237 [1.112-1.377]; 95% PI: 0.888-1.725; obesity: RR [95% CI] =  1.642 [1.466-1.839]; 95% PI: 1.143-2.358) and colorectal cancer (overweight: RR [95% CI] =  1.124 [1.056-1.197]; 95% PI: 0.931-1.357; obesity: RR [95% CI] =  1.366 [1.242-1.503]; 95% PI: 0.959-1.945) in the total population. Subgroup analysis revealed that overweight (RR [95% CI] =  1.237 [1.165-1.314]; 95% PI: 1.154-1.327) and obesity (RR [95% CI] =  1.306 [1.152-1.480]; 95% PI: 1.108-1.539) were associated with an increased risk of pancreatic cancer only in women, and overweight also increased the gastric cancer risk of women (RR [95% CI] =  1.041 [1.013-1.070], 95% PI: 0.806-1.230). No significant association of overweight/obesity and esophageal cancer was observed in both male and female. Conclusion Our study suggested that overweight/obesity elevated the risks of liver and colorectal cancer in both men and women. No significant association was found between overweight/obesity and the risk of developing esophageal cancer. Clinicians are advised to consider weight control as an effective measure for preventing pancreatic, liver, and colorectal cancers.